2020
DOI: 10.1111/dom.13952
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of insulin glargine 300 U/mL in insulin‐naïve patients with type 2 diabetes after failure of oral therapy in a real‐world setting

Abstract: Aim: To evaluate the effectiveness and safety of initiating basal insulin-supported oral therapy (BOT) with insulin glargine 300 U/mL (Gla-300) in patients with type 2 diabetes inadequately controlled on oral antidiabetic drugs (OADs). Materials and Methods:This non-interventional, multi-centre, prospective 52-week study, conducted in Germany and Switzerland, documented patients with type 2 diabetes with an HbA1c of between 7.5% and 10.0%, currently treated with OADs, after the physician had decided to start a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
15
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 14 publications
7
15
2
1
Order By: Relevance
“…However, there is a paucity of real-world comparative effectiveness research in European patient populations [ 26 ]. Non-comparative studies conducted in Europe have shown that switching to [ 27 29 ] or initiating [ 30 ] Gla-300 improves glycemic control, but the impact on hypoglycemia is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a paucity of real-world comparative effectiveness research in European patient populations [ 26 ]. Non-comparative studies conducted in Europe have shown that switching to [ 27 29 ] or initiating [ 30 ] Gla-300 improves glycemic control, but the impact on hypoglycemia is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The Toujeo-1 explored the real-world effectiveness of Gla-300 in adult patients with T2D uncontrolled on their previous OAD therapy with or without a Glucagon-Like Peptide1 Receptor Agonist (GLP-1 RA). 7 Investigators were general practitioners and specialists in internal medicine, endocrinology/diabetology. The Swiss cohort started Gla-300 treatment between November 2015 and December 2016 in 21 participating centers.…”
Section: Methodsmentioning
confidence: 99%
“…5,6 Toujeo-1 is a 12-month prospective real-world study to investigate the effectiveness and safety of Gla-300 in patients with T2D who were uncontrolled on oral antidiabetic drugs (OADs) ± Glucagon-Like Peptide-1 Receptor Agonists (GLP-1 RA). Data for the pooled patients from Germany and Switzerland have been published recently, 7 but data specific for Switzerland are lacking. It was therefore the purpose of the present analysis to provide Switzerland specific data and to put these data into perspective with the ones in the overall Toujeo-1 dataset.…”
Section: Introductionmentioning
confidence: 99%
“…in whom glycaemic targets have not been achieved) initiated on Gla-300 therapy, and had to have a duration of at least 24 weeks and individual participant-level data available for both efficacy and safety outcomes [16]. In the present analysis, 14 trials conducted between June 2015 and December 2018 were pooled (Table 1), ten of which are already published [17][18][19][20][21][22][23][24][25][26][27]. The rationale, methodology and a detailed description of the variables have been already provided in the published protocol of the REALI project [16].…”
Section: Study Selection and Populationmentioning
confidence: 99%